Opioid-Induced Constipation among a Convenience Sample of Patients with Cancer Pain - Coyne, Karin S.; Sexton, Chris; LoCasale, Robert J.; King, Frederic R.; Margolis, Mary Kay; Ahmedzai, Sam H. (Frontiers in Oncology, 2016)
Background: Little is known regarding the burden of opioid-induced constipation (OIC) among patients who suffer from cancer-related pain. Methods: A prospective longitudinal study was conducted among cancer patients in the United Kingdom (UK), Canada, and Germany, which included medical record data abstraction, Internet-based patient surveys, and physician surveys. Patients on daily opioid therapy (≥30 mg for ≥4 weeks) for treatment of cancer pain with self-reported OIC were recruited. Response to laxatives was defined by classifying participants into categories of laxative use and evaluating the prevalence of inadequate response. Descriptive statistics were used to evaluate outcomes, including the Patient Assessment of Constipation-Symptom (PAC-SYM), Patient Assessment of Constipation-Quality of Life (PAC-QOL), EuroQOL 5 Dimensions, and Global Assessment of Treatment Benefit, Satisfaction, and Willingness to Continue. Results: Recruitment was difficult for this study with only 31 participants completing the baseline survey and meeting criteria for opioid use and OIC (26 UK, 1 Canada, 4 Germany). 52% (n=16) of participants were male; all were white. Breast (23%, n=7), pancreatic (13%, n=4), and multiple myeloma (13%, n=4) were the most common cancers. Mean duration of chronic pain and opioid use were 2.3 and 1.3 years, respectively. Participants reported having a mean of 4.4 bowel movements/week in the two weeks prior to baseline, of which a mean of 0.9 were spontaneous. Most participants (90%, n=28) were using at least one lifestyle approach to manage their constipation; 65% (n=20) were taking ≥1 over the counter laxative; 19% (n=6) were taking ≥1 prescription laxative; 23% (n=7) reported no laxative use in the prior two weeks. Moderate–to-severe constipation symptoms on the PAC-SYM were common and mean scores on health-related quality of life outcomes were comparable to chronic pain populations. Conclusions: In this primarily UK sample, there appears to be considerable unmet OIC treatment needs among cancer patients.